Molecular dynamics study on the contribution of 4H–SiC surface morphology and crystal orientation to the wetting behavior of molten Al droplet - Lv, Yi; Peng, ChengCheng; Liao, Feng; Yang, Mo (Materials science in semiconductor processing, 2022)
AlSiC composites is a common material to make IGBT substrate due to its adjustable coefficient of thermal expansion which can be well matched with the chip and ceramic substrate to prevent the fatigue failure. Understanding the role of SiC surface morphology or crystal orientation might have an important influence on the proper control of the solid-liquid interface transmission in the process of preparing SiC reinforced aluminum matrix composites. To quantify the solid-liquid interaction, the molecular dynamics study is performed on the wetting characteristics of molten aluminum droplets on the 4H–SiC surface. Two SiC surface structures including rectangular-groove and wedge-groove are firstly adopted to analyze the effect of surface morphology on the wettability. Then, the wetting characteristics of Al droplets on two SiC crystal orientations including (110) plane and (111) plane are studied. The corresponding contact angles θ in the four Al/SiC systems are 124.81°, 126.65°, 105.72° and 97.35° respectively. It is found that the atomic surface morphology and crystal orientation playing important roles in the wettability of 4H–SiC. High hydrophobic is observed on the rectangular-groove and wedge-groove surface, while the wettability of the (110) plane and (111) plane is between wetting and hydrophobicity.